Social Responsibility and the Late Medieval Mystics - Petry, Ray C. (Church history, 1952)
Charges of social irresponsibility have frequently been hurled against the medieval mystics, in their own day as in our yet more activist age. Mysticism and monasticism, to whose discipline the mystics owed much, have often been condemned for selfish withdrawal from public obligation. A major cause of this unjustifiable indictment is doubtless traceable to a predominant area of ignorance within the Western World. This is the growing unawareness of the balance maintained in the Christian tradition between contemplative worship of the Divine and active service of the human.